A government innovation in housing the urban poor the Tondo experience - Reforma, Mila A. (Philippine Journal of Public Administration, 1978)
In order to alleviate the critical housing problem that the country faces today, an alternative approach has been implemented by the National Housing Authority (NHA) through the Tondo Foreshore/Dagat-Dagatan Development Project (TFDDP). This approach seeks, not urban poor relocation to distant sites, but on-site upgrading, utilizing the resources of the people in the execution of on-site improvements. There is maximum retention of structures and minimum displacement of families, maximum community participation in planning and implementation, and provision for basic services and utilities. The experience of the NHA in the first "reblocking" exercise is detailed here and the issues it raises especially as regards community participation and satisfaction are discussed.